Imagining Global Amsterdam History, Culture, and Geography in a World City - Waard, Marco de (Cities and Cultures, 2012)
Imagining Global Amsterdam brings together new essays on the image of Amsterdam as articulated in film, literature, art, and urban discourse, considered within the context of globalization and its impact on urban culture. Subjects include: Amsterdam's place in global cultural memory; expressions of global consciousness in Amsterdam in the 'Golden Age'; articulations of Amsterdam as a tolerant, multicultural, and permissive 'global village'; and globalization's impact 'on the ground' through city branding, the cultural heritage industry, and cultural production in the city. Written by an interdisciplinary team of scholars, and united by a broad humanities approach, this collection forms a multifaceted inquiry into the dynamic relationship between Amsterdam, globalization, and the urban imaginary.